(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article presents the fact that unevenness has negative properties of products produced in a spinning enterprise, often negatively affects the technical and economic indicators of the enterprise, as well as the physical and mechanical properties of yarn, the importance of testing and controlling unevenness of products in spinning production, and the causes and timing of unevenness are determined.